2022
DOI: 10.3390/v14020294
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of SARS-CoV-2 Variant Omicron with a Doubling Time of 2.0–3.3 Days Can Be Explained by Immune Evasion

Abstract: Omicron, the novel highly mutated SARS-CoV-2 Variant of Concern (VOC, Pango lineage B.1.1.529) was first collected in early November 2021 in South Africa. By the end of November 2021, it had spread and approached fixation in South Africa, and had been detected on all continents. We analyzed the exponential growth of Omicron over four-week periods in the two most populated of South Africa’s provinces, Gauteng and KwaZulu-Natal, arriving at the doubling time estimates of, respectively, 3.3 days (95% CI: 3.2–3.4 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 24 publications
5
57
0
Order By: Relevance
“…For example, it is estimated that the first case of Omicron in South Africa occurred on approximately October 9, 2021 (16). It was first identified on November 9, 2021 and reported to the WHO two weeks later, after identification of its numerous amino acid changes (17). Two days later it was classified as a variant of concern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is estimated that the first case of Omicron in South Africa occurred on approximately October 9, 2021 (16). It was first identified on November 9, 2021 and reported to the WHO two weeks later, after identification of its numerous amino acid changes (17). Two days later it was classified as a variant of concern.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming all vaccinated individuals receive a variant-specific booster series and all unvaccinated individuals receive a variant-specific primary series, a variant-chasing vaccine strategy could avert over 40% of deaths if it is rolled out on a large scale within 5 days from introduction of the new variant, and has a 20-day window in which it would avert more deaths than the same coverage levels with currently available vaccines. The date of introduction of a new variant into a population is impossible to know, but Omicron’s first case was estimated to occur a month before it was first detected (16; 17). Using this lag-time, if it takes 30 days to identify a new variant, the percentage of deaths a variant-chasing vaccine strategy could avert would fall to below 20%, before considering the time it would take to develop and deploy a vaccine after identification.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary data indicate increased transmissibility and risk of reinfection, with the number of cases caused by the Omicron variant increasing in almost all South African provinces. Studies from South Africa and the UK reported doubling times of 3.38 days and 2–2.5 days, respectively, with the basic reproduction number (R0) above 3 and an estimated weekly increase in the Omicron-to-Delta ratio in the range of 7.2–10.2, which was considerably higher than the increase in the ratio of Delta to Alpha (estimated to be in in the range 2.5–4.2) [ 107 , 108 ]. However, the current limited and preliminary evidence suggests that Omicron has a less severe clinical presentation, presenting as a mild disease with predominantly upper respiratory symptoms such as muscle aches and fatigue for 1 to 2 days, headache, itchy throat, slight cold, or mild cough [ 109 , 110 ].…”
Section: How Variants Affect the Efficacy Of Sars-cov-2 Vaccinesmentioning
confidence: 99%
“…Many countries have experienced their second, third and fourth waves in terms of cases and resultant deaths. [1][2][3][4] The outbreak of the new Omicron variant in different countries [5][6][7] is of global concern, [8] as it threatens the return to normalcy and the ongoing COVID-19 vaccination programmes. Non-pharmaceutical interventions to minimise the spread of infections included travel restrictions, lockdowns, physical distancing, regular handwashing and wearing of face masks.…”
Section: Introductionmentioning
confidence: 99%